2002
DOI: 10.1021/jp025873p
|View full text |Cite
|
Sign up to set email alerts
|

Study of Argon Adsorbed on Open-Ended Carbon Nanotube Bundles

Abstract: The adsorption of Ar on open-ended single-walled carbon nanotube bundles was studied. The amount of argon, which corresponds to the first coverage adsorbed on open-ended carbon nanotube bundles, was about 3 mmol/g. The isosteric heat of adsorption was obtained from the isothermal adsorption measurement in the low coverage region performed at temperatures ranging from 120 to 135 K. The estimated heat of adsorption of argon in the low-coverage region was 182 meV and was comparable to that of nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…In recent years, carbon nanotubes 42 have stimulated considerable interest, including potential use for membrane adsorption and separation due to their well-defined nanoscale structures. 43 Experimental studies have been reported on the adsorption of simple pure gases, such as N 2 , 44-51 O 2 , 49 Ar, 52 Kr, 53 Xe, 54 77 and of a N 2 -O 2 mixture ͑representing air͒ by GCMC simulation. 78 Competitive adsorption was observed in these studies, and it has been suggested that carbon nanotubes could be a superior adsorptive media to separate gas mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbon nanotubes 42 have stimulated considerable interest, including potential use for membrane adsorption and separation due to their well-defined nanoscale structures. 43 Experimental studies have been reported on the adsorption of simple pure gases, such as N 2 , 44-51 O 2 , 49 Ar, 52 Kr, 53 Xe, 54 77 and of a N 2 -O 2 mixture ͑representing air͒ by GCMC simulation. 78 Competitive adsorption was observed in these studies, and it has been suggested that carbon nanotubes could be a superior adsorptive media to separate gas mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of experimental studies have already been carried out on the adsorption of small molecules (Kuznetsova et al 2000;Muris et al 2000;Yoo et al 2002aYoo et al , 2002bCinke et al 2003) and larger organic vapors (Hilding et al 2001;Agnihotri et al 2005b) on various carbon nanotubes, single-or multiwalled, closed-or open-ended. Molecular simulations have also been performed to study gas adsorption on carbon nanotubes (Simonyan et al 1999;Yin et al 1999;Williams and Ecklund 2000;Duren and Keil 2001;Calbi et al 2001;Talapatra and Migone 2002;Levesque et al 2002;Ohba and Kaneko 2002;Zhang and Wang 2002;Shi and Johnson 2003;Jiang and Sandler 2003;Agnihotri et al 2005a;Jiang et al 2005), but very few have addressed phase transitions inside nanotubes (Peterson et al 1990; Maddox and Gubbins 1995;Jiang et al 2004).…”
mentioning
confidence: 99%
“…The isosteric heat of argon adsorption in cylindrical pores has been studied both experimentally and theoretically (Wilson et al 2002;Yoo et al 2002;Bienfait et al 2004;Jakubek and Simard 2004;Urban et al 2005;Do et al 2008a). However, all of these studies dealt with bundles of SWCNTs and MWCNTs, where the initial isosteric heat is due to adsorption in the interstices between the tubes and in the grooves on the boundary of the bundle (Urban et al 2005).…”
Section: Isosteric Heatsmentioning
confidence: 99%